Review of 2022 WHO guidelines on the control and elimination of schistosomiasis. Issue 11 (November 2022) - Lo, Nathan C; Bezerra, Fernando Schemelzer Moraes; Colley, Daniel G; Fleming, Fiona M; Homeida, Mamoun; Kabatereine, Narcis; Kabole, Fatma M; King, Charles H; Mafe, Margaret A; Midzi, Nicholas; Mutapi, Francisca; Mwanga, Joseph R; et al.
Summary: Schistosomiasis is a helminthiasis infecting approximately 250 million people worldwide. In 2001, the World Health Assembly (WHA) 54.19 resolution defined a new global strategy for control of schistosomiasis through preventive chemotherapy programmes. This resolution culminated in the 2006 WHO guidelines that recommended empirical treatment by mass drug administration with praziquantel, predominately to school-aged children in endemic settings at regular intervals. Since then, school-based and community-based preventive chemotherapy programmes have been scaled-up, reducing schistosomiasis-associated morbidity. Over the past 15 years, new scientific evidence—combined with a more ambitious goal of eliminating schistosomiasis and an increase in the global donated supply of praziquantel—has highlighted the need to update public health guidance worldwide. In February, 2022, WHO published new guidelines with six recommendations to update the global public health strategy against schistosomiasis, including expansion of preventive chemotherapy eligibility from the predominant group of school-aged children to all age groups (2 years and older), lowering the prevalence threshold for annual preventive chemotherapy, and increasing the frequency of treatment. This Review, written by the 2018–2022 Schistosomiasis Guidelines Development Group and its international partners, presents a summary of the new WHO guideline recommendations for schistosomiasis along with their historical context, supporting evidence, implications for public health implementation, and future research needs.